2015
DOI: 10.17221/125/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion treatment on the thermal stability and structure of corn starch with different emulsifiers

Abstract: Corn starch was treated with raw moisture (30%), screw speed (160 rpm), extrusion temperature (30, 55, 80, 105, 130, and 155°C), and emulsifier (1.2%) to produce the starch extrudate particles in a twin screw extruder. The influence of extrusion processing and composition (starch and emulsifier content) on the viscosity, microstructure, solubility, swelling power, and thermal stability of starch extrudate particles was examined. The SEM results showed that the surface of starch extrudate particles was quite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
4
16
0
1
Order By: Relevance
“…Figure c reveals the best treatment for RS production: 18% moisture content and 5.1% of citric acid with the yield of 1.15 g 100 g −1 (Table ), and Figure d shows the optimized conditions of ECP at 21.4% moisture content with 2.18% of citric acid, generating RS at 0.85 g 100 g −1 ( Figure ); both treatments were carried out at 127 °C and 233 rpm. As presented in Figure c,d, the granular structure of corn starch was destroyed and generated amorphous structures owing to gelatinization and dextrinization of starch because of high temperature, mechanical stress, and high pressure during extrusion . RS is visible on the surface of the structures in the form of a dense aggregate due to the leaching of amylose out of the starch granules during ECP …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure c reveals the best treatment for RS production: 18% moisture content and 5.1% of citric acid with the yield of 1.15 g 100 g −1 (Table ), and Figure d shows the optimized conditions of ECP at 21.4% moisture content with 2.18% of citric acid, generating RS at 0.85 g 100 g −1 ( Figure ); both treatments were carried out at 127 °C and 233 rpm. As presented in Figure c,d, the granular structure of corn starch was destroyed and generated amorphous structures owing to gelatinization and dextrinization of starch because of high temperature, mechanical stress, and high pressure during extrusion . RS is visible on the surface of the structures in the form of a dense aggregate due to the leaching of amylose out of the starch granules during ECP …”
Section: Resultsmentioning
confidence: 97%
“…As presented in Figure 4c,d, the granular structure of corn starch was destroyed and generated amorphous structures owing to gelatinization and dextrinization of starch because of high temperature, mechanical stress, and high pressure during extrusion. [2,13,27,43] RS is visible on the surface of the structures in the form of a dense aggregate due to the leaching of amylose out of the starch granules during ECP. [37,44]…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…It is well known that, chitosan exhibits characteristic peaks at 2θ = 10° and 20°, and the XRD pattern of the native corn starch shows peaks at 2θ of 15°, 17°, 18°, and 23° (Gutha, Janak, Zhang, Zhang, & Xu, 2017; Yang et al., 2015). It can be seen that the peak of chitosan at 2θ = 10° and almost all characteristic crystalline peaks of native corn starch disappeared in the XRD of TETA‐WICF/MCR (shown in Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that most of the native starch granules were spherical, elliptical, and polygonal, with a particle distribution size of 5-16 μm, similar to that of most other grains. Scanning Journal of Chemistry electron microscopy displayed cracking of starch granules with extrusion [38]. e microstructure and particle morphology of the powder may be related to changes in extrusion parameters.…”
Section: Microscopic Structuresmentioning
confidence: 96%